Empowering EFL students: A review of student-centred learning effectiveness and impact - Pastini, Ni Wayan; Lilasari, Luh Nyoman Tri (Politeknik Negeri Bali, 2023)
In the dynamic landscape of education, the paradigm shift towards student-centred learning (SCL) has emerged as a pivotal pedagogical approach, particularly in the context of EFL, the study of English for non-native speakers. This review explores the background and urgency of comprehending the effectiveness and impact of student-centred learning methods in enhancing students' empowerment within the EFL domain. The pressing need for this exploration arises from the imperative to tailor educational practices to meet the diverse learning needs of contemporary students, equipping them for a rapidly changing and complex global environment. Employing a comprehensive review methodology, this study synthesizes insights from a diverse array of prior research on SCL, specifically within EFL settings. Literature spanning various educational contexts, disciplines, and levels is systematically analysed to distil overarching conclusions about the effectiveness and impact of student-centred approaches in EFL instruction. The review critically examines methodologies, sample sizes, and key findings from selected studies, offering a nuanced understanding of the existing body of knowledge within the specific context of English proficiency development for diverse learners. The analysis focuses on key themes emerging from the reviewed literature, including student engagement, motivation, learning outcomes, and the development of critical thinking skills in the EFL context. Through a comparative lens, the review identifies patterns, trends, and gaps in the current understanding of SCL's impact on EFL education. Special attention is given to variations in outcomes based on educational levels, language proficiency levels, and cultural contexts specific to EFL instruction. Drawing on the synthesized evidence, the review concludes with insights into the overall effectiveness of SCL approaches in teaching and studying of English for non-native speakers. It underscores the positive impact on student motivation, language proficiency, and the cultivation of essential skills for lifelong language learning. The review also acknowledges challenges unique to EFL contexts and suggests areas requiring further investigation, contributing to the ongoing discourse on optimizing student-centred methodologies in language education. The pedagogical impact of this review lies in its potential to inform EFL educators, policymakers, and researchers about the nuanced benefits of adopting student-centred learning practices specifically tailored for English language instruction. By synthesizing diverse findings within the EFL context, the study offers practical insights into designing and implementing effective student-centred strategies for teaching English for non-native speakers., thus contributing to the advancement of language education practices.